Avaliação ecotoxicológica de solos sob cultivo convencional de tomate e morango - Marin, Ericka Broetto (2013)
Pesticides can directly interfere with the food chain, by providing an ecological imbalance. Therefore, studies are needed to verify in field if these compounds are being applied to the soil at concentrations that do not affect the terrestrial and aquatic